Public Images of Dairy Farms among Urban Dwellers in Bogotá, Colombia - Wellbrock, Wiebke; Burkart, Stefan; Enciso, Karen; Knierim, Andrea (CENTMA Research, 2019)
This study explores the public images of dairy farms among urban dwellers in Bogotá, Colombia. For the study, d esigned as an explorative case study, 30 participants were interviewed using a triangulated research method including a word association task, a drawing exercise, and a semi -structured interview. Public images reflected traditional dairy farms and were constructed through personal experiences with peasants and traditional manors. Product choice was based on health and hygiene, associated with modern dairy farms. Yet, modernization was argued to threaten animal welfare, the environment, and peasant livelihoods. To ensure socio-cultural sustainability, traditional production systems need to be better integrated into the modernization process.